ANALISIS TRANSPARANSI DAN AKUNTABILITAS LKS-PWU (STUDI KASUS PT BANK KB BUKOPIN SYARIAH DAN PT BANK CIMB NIAGA SYARIAH) - Nur Azizah; Sugiarti Fatma Laela; Sigid Eko Pranomo (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2026)
This study aims to analyze the level of transparency and accountability of Islamic financial institutions receiving cash waqf based on Government Regulation No. 42 of 2006 and OJK Circular Letter No. 10/SEOJK.03/2020. This research is a qualitative descriptive study with the main data sources used, namely primary data and secondary data as supporting data for the research. This study uses a case study approach on 2 LKS-PWU, namely PT Bank KB Bukopin Syariah (BUS) and PT Bank CIMB Niaga Syariah (UUS). This study uses data collection techniques in the form of observation, structured interviews, and research questionnaires. This study uses analysis techniques in the form of data reduction, data presentation, and drawing conclusions. This study shows that the level of transparency of LKS-PWU based on PP No. 42 of 2006 and SEOJK No.10 / SEOJK.03 / 2020 is optimal towards very optimal with an average value of 4.45 or equivalent to 89%. In addition, the level of accountability of LKS-PWU is also optimal towards very optimal with an average value of 4.44 or equivalent to 89%. Things that still need to be improved by LKS-PWU are education to wakif and prospective wakif through social media (website, Instagram, and Facebook) and increased supervision of LKS-PWU management. In addition, there needs to be standardization and supervision carried out by the regulator.